Obstacles to Disinflation : What is the Role of Fiscal Expectations? - Gelos, R. (IMF Working Papers; Working Paper, 2004)
Is backward-looking behavior in pricing or imperfect credibility of stabilization efforts responsible for the failure of inflation rates to decline to targeted levels during many disinflation programs? This paper assesses the relative importance of these two factors during a number of disinflation attempts in developing and transition economies. Using survey data, we find that expectations of future inflation play a much more important role than past inflation in shaping the inflation process. We also find that an improvement in primary fiscal balances significantly reduces inflation expectations. This suggests that during stabilization episodes, priority should be given to building fiscal credibility by strengthening public finances.